Vertical Structure of the Arctic Spring Transition in the Middle Atmosphere - Matthias, Vivien; Stober, Gunter; Kozlovsky, Alexander; Lester, Mark; Belova, Evgenia; Kero, Johan (FID GEO, 2021)
In the middle atmosphere, spring transition is the time period where the zonal circulation reverses from winter westerly to summer easterly which has a strong impact on the vertical wave propagation influencing the ionospheric variability. The spring transition can be rapid in form of a final sudden stratospheric warming (SSW, mainly dynamically driven) or slow (mainly radiatively driven) but also intermediate stages can occur. In most studies spring transitions are classified either by their timing of occurrence or by their vertical structure. However, all these studies focus exclusively on the stratosphere and it is not clear if and how pre‐winter conditions have an impact on when and how spring transitions take place. Here we classify the spring transitions regarding their vertical‐temporal development beginning in January and spanning the whole middle atmosphere in the core region of the polar vortex. This leads to five classes where the timing of the SSW in the preceding winter and a downward propagating Northern Annular Mode plays a crucial role. First, we use Microwave Limb Sounder satellite data to describe the five classes for recent single years, and then we use Modern‐Era Retrospective analysis for Research and Applications Version 2 reanalysis data for a composite analysis. The results show distinctive differences between the five classes in the months before the spring transition especially in the mesosphere. We hypothesize that this will help to improve the prediction of the spring transition. Additionally, meteor radar winds are used to link spring transition effects in the upper mesosphere and lower thermosphere with the stratospheric final warming. : Plain Language Summary: Springtime is characterized by a dramatic change in circulation from winter westerly to summer easterly in the Arctic middle atmosphere (20–100 km). The timing and structure of this change process largely varies from year to year. In most studies spring transitions are classified either by their timing of occurrence or, slightly less common, by their vertical structure. However, all these studies focus on the stratosphere (20–50 km) only and do not consider a large part of the spring transitions because they only investigating for example, particularly early or late occurring spring transitions. Here we classify the spring transitions regarding their vertical and temporal development already starting in mid‐winter. This leads to five classes where the timing of large polar vortex disturbances in the preceding winter as well as the vertical structure of the polar vortex plays a crucial role. This allows a certain prediction at least for some of the five spring transition classes. Additionally, the spring transition in the upper mesosphere and lower thermosphere (80–100 km) is investigated regarding the new spring transition classes and its impact on the ionosphere and therefore on our communication and navigation system is discussed. : Key Points: There are five new classes of spring transitions in the middle atmosphere. The classification uses the temporal‐vertical structure of zonal wind and Northern Annular Mode starting in January. The classification enables a better understanding of the timing and type of the spring transition. : European Community Horizon 2020